Cross‐sectional and comparative analysis of videos on erectile dysfunction treatment on YouTube and TikTok. (4th February 2022) - Babar, Mustufa; Loloi, Justin; Patel, Rutul D.; Singh, Sandeep; Azhar, Umair; Maria, Pedro; Small, Alexander; Watts, Kara
Abstract: The aim of this study was to evaluate the quality of information regarding erectile dysfunction (ED) treatment on YouTube and TikTok. The term "erectile dysfunction" was searched on YouTube and TikTok in July 2021. The first 50 videos on each platform that met inclusion were included. Videos were sorted as reliable or unreliable based on accuracy of video content. Quality of information was evaluated using Patient Education Materials Assessment Tool (PEMAT) and 5‐point modified DISCERN. TikTok videos were shorter (0.4 minutes vs. 5.2 minutes, p < 0.001) and had more likes (2294 vs. 1000, p = 0.005), views per month (17, 281 vs. 3521, p < 0.001) and subscribers/followers (97, 500 vs. 23, 000, p = 0.016) than YouTube videos. TikTok videos were less reliable than YouTube videos (TikTok 5/50 [10%] vs. YouTube 21/50 [42%], p < 0.001). YouTube mentioned more about phosphodiesterase type 5 inhibitors (32% vs. 10%, p = 0.007), while TikTok mentioned more about alternative supplements (36% vs. 4%, p < 0.001). YouTube had a higher DISCERN (1.99 vs. 0.98, p < 0.001) and PEMAT actionability scores (64.2% vs. 54.0%, p = 0.039) when compared to TikTok. YouTube videos were of higher quality than TikTok videos. Nevertheless, YouTube had a considerable amount of unreliable information. We recommend a collaborative effort from the medical community to improve information regarding ED treatment on YouTube and TikTok.